ХАРГАНАТЫН АМ ОРЧМЫН ВУЛКАНОГЕН ЧУЛУУЛГИЙН БОДИСЫН НАЙРЛАГА, ГАРАЛ ҮҮСЭЛ - А., Тулга; Ц., Наранцэцэг; Г., Азжаргал (Geological Issues, 2022)
In this study, we report on U-Pb dating, major and trace elements with aim constraining the tectonic setting of early carboniferous volcanic rocks near the Harganaty Am valley of Southern Mongolia. These volcanic rocks, which are mainly composed of basalt, basaltic andesite, andesite, rhyodacite and rhyolite, located in the eastern segment of Gobi-Tianshan between the Gurvansaikhan terrane and the Tsagaan Uul block. The result of LA-ICPMS zircon dating for two felsic rocks indicate that formed in the early carboniferous (ca. 325-333 Ma). The mafic and intermediate rocks have SiO2 = 41.3-57.7 wt.%, K2O = 0.5-2.54 wt.%, Mg#=0.41- 0.57, Cr = 11-122 ppm, Ni = 4.82-188 ppm, whereas the felsic rocks have SiO2 = 41.3-57.7 wt. %, K2O = 2.1-4.86 wt. % Mg#=0.41-0.57, Cr = 10-91 ppm, Ni = 0.8-17.88 ppm. These data are typically calc-alkaline suite. The mafic to intermediate rocks are characterized by strong enrichment in large ion lithophile elements (LILE) such as Rb, Ba, Sr and Pb, depletion in high field strength elements (HFSEs) such as Nb, Ta and Ti, depletion in heavy rare-earth elements (HREEs), and positive Eu anomalies (Eu/Eu* = 1.72). On the other hand, the felsic rocks show a strong depletion in Nb, Ta, Sr, P, and Ti, enrichment in Th, Rb, and, Ba, and relatively negative Eu anomalies (Eu/Eu* = 0.56-0.74). Taken together, these data suggest that the mafic to felsic volcanic rocks derived from the partial melting of newly accreted crust. The early carboniferous volcanic rocks indicate an extensional environment, similar to a subduction related rocks from orogenic belts.